Praseodymium-doped sodium niobate-barium titanate-based stress luminescent material and preparation method thereof
Through the stress luminescent material doped with praseodymium sodium niobate-barium titanate, combined with ball mill mixing and high-temperature solid-phase sintering technology, the stability and environmental pollution of existing stress luminescent materials are solved, and the effect of high luminescent intensity and good stability is achieved.
Patent Information
- Application Number
- CN202411659992.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
AI Technical Summary
Existing stress luminescent materials have problems such as deliques, unstable chemical properties and environmental pollution in their applications, and their application scope is limited.
Using praseodymium-doped sodium niobate-barium titanate as stress luminescent material, stress luminescent materials with high luminescent intensity and good optical properties are prepared through ball milling mixing and high-temperature solid phase sintering process.
It achieves high luminous intensity and good physical and chemical stability of the material, and is environmentally friendly in the process, and is suitable for the new generation of high-tech fields.
Smart Images

Figure CN119505900A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inorganic luminescent materials, and in particular to a praseodymium-doped sodium niobate-barium titanate stress luminescent material and a preparation method thereof. Background Art
[0002] Stress luminescence (ML) is a phenomenon in which an object converts mechanical energy into photons and releases energy to the outside when it is subjected to external mechanical forces such as friction, compression, ultrasound, torsion, and stretching. Photoluminescence is a phenomenon in which an object relies on external light sources to obtain energy, which leads to excitation and luminescence. Stress luminescent materials have stress-light conversion characteristics, which convert mechanical energy into light energy under stress. This characteristic makes stress luminescent materials have very wide application value in important scientific and technological fields such as optoelectronic components, stress distribution visualization, and information optical display.
[0003] In the past 10 years, researchers have discovered a series of stress luminescent materials, such as SrMg2(PO4)2∶Eu (purple), CaYAl3O7∶Eu (blue), and CaZnOS∶Cu (cyan). However, the stress luminescent materials that can be used in practice are limited to SrAl2O4:Eu. 2+ , ZnS:Cu, etc. The stress luminescent materials of the aluminate system are easy to deliquesce and have unstable chemical properties; the synthesis of the stress luminescent materials of the sulfide system requires sintering under a protective atmosphere, and the environment will be polluted during the preparation process.
[0004] Alkaline niobate materials have excellent ferroelectric, piezoelectric, electro-optical, acousto-optic and nonlinear optical properties, as well as excellent mechanical, thermal and chemical stability. Compared with aluminates and aluminate systems, they are more environmentally friendly and are the most attractive host material candidates for the preparation of stress luminescent materials. Summary of the invention
[0005] The invention provides a praseodymium-doped sodium niobate-barium titanate stress luminescent material with high luminescent intensity and a preparation method thereof.
[0006] The technical solution provided by the present invention is a praseodymium-doped sodium niobate-barium titanate stress luminescent material, which is composed of phosphor and polymer material. The chemical formula of the phosphor is: Na 0.991-x Ba x Pr 0.003 Nb 1-x Ti x O3, x represents the mole fraction, 0.005≤x≤0.025;
[0007] The polymer material is composed of epoxy resin and polyetheramine, and the mass ratio of the two is 3 to 10:1;
[0008] The weight ratio of the fluorescent powder to the polymer material is 1:1-5.
[0009] The present invention Na 0.991-x Ba x Pr 0.003 Nb 1-x Ti x The crystal structure of O3 is orthorhombic (space group P21ma), and Ba 2+ , Pr 3+ Replace Na + The position of Na 0.991-x Ba x Pr 0.003 Nb 1-x Ti x O3 has photoluminescence properties, the best excitation wavelength is 328nm, and the luminescent color is orange-red.
[0010] The stress luminescent material of the present invention has stress luminescent performance under friction and compression conditions, with an emission band of 580-650nm and an emission center of orange-red light at 610nm.
[0011] The present invention also provides a method for preparing the above-mentioned praseodymium-doped sodium niobate-barium titanate stress luminescent material, comprising the following steps:
[0012] 1) Carbonates Na2CO3, BaCO3, oxide Pr6O 11 , TiO2, Nb2O5 according to the chemical formula Na 0.985- x Ca x Pr 0.005 Nb 1-x Ti x O3 is used for mixing, anhydrous ethanol is used as a solvent for ball milling, and then the phosphor powder is obtained by drying after being taken out, firing for the first time, cooling, grinding for the first time, firing for the second time, cooling, and grinding for the second time.
[0013] 2) mixing epoxy resin and polyetheramine according to a proportion to obtain a polymer material;
[0014] 3) Pour the formulated amount of phosphor and polymer material into the mold in sequence, let it stand, dry, and demould to obtain the stress luminescent material.
[0015] In step 1), the ball milling is carried out at a ball milling speed of 100 to 300 r / min for 2 to 12 hours.
[0016] In step 1), the first firing is to increase the temperature to 700-900° C. at a rate of 3-10° C. / min and keep the temperature for 3-9 hours.
[0017] In step 1), the second firing is carried out at 1050-1200° C. for 2-6 hours.
[0018] In step 1), the first grinding time and the second grinding time are both 30 to 60 minutes.
[0019] In step 2), the epoxy resin and the polyetheramine are mixed and stirred until no bubbles are generated, and vaseline is evenly applied on the inner surface of the polytetrafluoroethylene mold to prevent the polymer material from sticking.
[0020] In step 3), the standing time is 10 to 20 minutes.
[0021] In step 3), the drying temperature is 50-80° C. and the drying time is 6-12 hours.
[0022] The present invention has the following beneficial effects:
[0023] 1) The stress luminescent material of the present invention combines ball milling mixing and high-temperature solid-phase sintering, so that the raw materials are mixed more evenly and can be mixed on a large scale. In addition, the oxide material is non-toxic and environmentally friendly. At the same time, it has excellent optical properties and has very good application prospects in new generation high-tech fields such as optical stress sensing.
[0024] 2) The present invention precisely controls the Na / Ba / Nb / Ti molar ratio so that the material has photoluminescence properties and effectively improves the stress luminescence properties of the material.
[0025] 3) The barium titanate in the present invention is insoluble in water, resistant to sulfuric acid corrosion, has a melting point of 1618°C, good high temperature stability, and stable physical and chemical properties, which relatively improves the physical and chemical stability of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The XRD test spectra of the phosphors of Examples 1 to 5 and Comparative Example 1 are shown;
[0027] Figure 2 The normalized PLE and PL diagrams of the phosphor of comparative example 1;
[0028] Figure 3 The friction stress luminescence spectrum of the stress luminescence material of comparative example 1;
[0029] Figure 4 1 is a normalized PLE and PL diagram of the phosphor of Example 1;
[0030] Figure 5 The friction stress luminescence spectrum of the stress luminescence material of Example 1;
[0031] Figure 6 1 is a normalized PLE and PL diagram of the phosphor of Example 2;
[0032] Figure 7 The friction stress luminescence spectrum of the stress luminescence material of Example 2;
[0033] Figure 8 3 are normalized PLE and PL diagrams of the phosphor of Example 3;
[0034] Fig. 9 The friction stress luminescence spectrum of the stress luminescence material of Example 3;
[0035] Fig.10 1 is a normalized PLE and PL diagram of the phosphor of Example 4;
[0036] Fig.11 The friction stress luminescence spectrum of the stress luminescence material of Example 4;
[0037] Fig.12 1 is a normalized PLE and PL diagram of the phosphor of Example 5;
[0038] Fig.13 This is the friction stress luminescence spectrum of the stress luminescent material of Example 5. DETAILED DESCRIPTION
[0039] The present invention will be further described below with reference to examples, but the present invention is not limited to these examples.
[0040] Example 1
[0041] 1) According to the chemical formula Na 0.986 Ba 0.005 Pr 0.003 Nb 0.995 Ti 0.005 O3 was used for batching, and 5.2252g Na2CO3 and 0.0511g Pr6O 11 , 0.0987g BaCO3, 0.0399g TiO2 and 13.2240g Nb2O5, placed in an agate ball mill, 80ml anhydrous ethanol was added dropwise, and the ball mill was performed at a speed of 100-300r / min for 2h, taken out and dried, and placed in an oven, heated to 700℃ at a rate of 3℃ / min and kept warm for 3h, cooled, ground for 30min, placed in an oven again, kept warm at 1050℃ for 2h, cooled, and ground for 30min, to obtain phosphor (abbreviated as NPN-0.005BT);
[0042] 2) Mix epoxy resin and polyetheramine in a mass ratio of 3:1, and stir until no bubbles appear in the mixed liquid to obtain a polymer material;
[0043] 3) The phosphor and polymer material are mixed in a mass ratio of 1:1, and 1.2 g of phosphor and 1.2 g of polymer are weighed respectively;
[0044] 4) After evenly applying vaseline on the inner surface of the polytetrafluoroethylene mold, 1.2 g of phosphor was spread on the bottom of the mold, and then 1.2 g of polymer material was added. The mold was allowed to stand at room temperature for 10 min, transferred to an oven, and baked at 50°C for 6 h. After drying, the mold was demolded to obtain the stress luminescent material.
[0045] In order to prove the phase of NPN-0.005BT, XRD test was carried out. Figure 1 The characteristic diffraction peaks of NPN-0.005BT shown are consistent with the standard peaks of NaNbO3, the crystal structure is an orthorhombic phase structure, the space group is P21ma, the doping of BaTiO3 does not affect the synthesis of the crystal phase, and no other impurity phases are observed.
[0046] In order to prove the photoluminescence performance of NPN-0.005BT, PLE and PL tests were carried out. The test results are shown in Figure 4 The excitation spectrum of NPN-0.005BT was obtained under the monitoring wavelength of 610nm. The optimal excitation wavelength was selected as 328nm. The emission wavelength was 580-650nm, which is Pr 3+ of 1 D2- 3 H4 transition, the luminescent color is orange-red.
[0047] In order to prove the stress luminescence performance of stress luminescence materials, conventional stress luminescence tests were carried out. The specific method was as follows: irradiation for 10 minutes under ultraviolet light with a wavelength of 254nm, and then standing in a dark environment for 2 minutes after pre-irradiation. The stress luminescence material was rubbed under a friction force of 15N to test the friction stress luminescence performance. The specific test results are shown in Figure 2. Figure 5 shown.
[0048] Example 2
[0049] 1) According to the chemical formula Na 0.981 Ba 0.01 Pr 0.003 Nb 0.99 Ti 0.01 O3 was used to prepare the ingredients, and 5.1987g Na2CO3, 13.1576g Nb2O5, 0.1973g BaCO3, 0.0799g TiO2 and 0.0511g Pr6O 11Place in an agate ball mill, add 80 ml of anhydrous ethanol, ball mill at a speed of 300 r / min for 12 hours, take out and dry, put into an oven, heat to 900°C at a rate of 10°C / min and keep warm for 9 hours, cool, grind for 60 minutes, put into the oven again, keep warm at 1200°C for 6 hours, cool, grind for 60 minutes, and obtain phosphor (abbreviated as NPN-0.01BT);
[0050] 2) Mix epoxy resin and polyetheramine in a mass ratio of 10:1, and stir until no bubbles appear in the mixed liquid to obtain a polymer material;
[0051] 3) The phosphor and polymer materials are mixed in a mass ratio of 1:5, and 1.2 g of phosphor and 6 g of polymer materials are weighed respectively for later use;
[0052] 4) After evenly applying vaseline on the inner surface of the polytetrafluoroethylene mold, 1.2 g of phosphor was spread on the bottom of the mold, and 6 g of polymer material was added. The mold was allowed to stand at room temperature for 20 min, transferred to an oven, and baked at 80°C for 12 h. After drying, the mold was demolded to obtain the stress luminescent material.
[0053] In order to prove the physical phase of NPN-0.01BT, XRD test was carried out. Figure 1 The characteristic diffraction peaks of NPN-0.01BT shown are consistent with the standard peaks of NaNbO3.
[0054] In order to prove the photoluminescence performance of NPN-0.01BT, PLE and PL tests were carried out. The test results are shown in Figure 6 The excitation spectrum of NPN-0.01BT was obtained under the monitoring wavelength of 610nm. The optimal excitation wavelength was selected as 328nm. The emission wavelength was 580-650nm, which is Pr 3+ of 1 D2- 3 H4 transition, the luminescent color is orange-red.
[0055] In order to prove the stress luminescence performance of stress luminescence materials, conventional stress luminescence tests were carried out. The specific method was as follows: irradiation for 10 minutes under ultraviolet light with a wavelength of 254nm, and then standing in a dark environment for 2 minutes after pre-irradiation. The stress luminescence material was rubbed under a friction force of 15N to test the friction stress luminescence performance. The specific test results are shown in Figure 2. Figure 7 shown.
[0056] Example 3
[0057] 1) According to the chemical formula Na 0.976 Ba 0.015 Pr 0.003 Nb 0.985Ti 0.015 O3 was used to prepare the ingredients, and 5.1723g Na2CO3, 13.0911g Nb2O5, 0.2960g BaCO3, 0.1198g TiO2, and 0.0511g Pr6O 11 , put it in an agate ball mill, add 80 ml of anhydrous ethanol, ball mill for 6 hours at a speed of 100-300 r / min, take it out and dry it, put it into an oven, heat it to 800℃ at a rate of 5℃ / min and keep it warm for 6 hours, cool it, grind it for 50 minutes, put it into the oven again, keep it warm at 1100℃ for 4 hours, cool it, grind it for 45 minutes, and get the phosphor (abbreviated as NPN-0.015BT);
[0058] 2) Mixing epoxy resin and polyetheramine in a mass ratio of 6:1, stirring until no bubbles appear in the mixed liquid, to obtain a polymer material;
[0059] 3) The phosphor and polymer material are mixed in a mass ratio of 1:4, and 1.2 g of phosphor and 4.8 g of polymer material are weighed for later use;
[0060] 4) After evenly applying vaseline on the inner surface of the polytetrafluoroethylene mold, 1.2 g of phosphor was spread on the bottom of the mold, and 4.8 g of polymer material was added. The mold was allowed to stand at room temperature for 15 min, transferred to an oven, and baked at 70°C for 9 h. After drying, the mold was demolded to obtain the stress luminescent material.
[0061] In order to prove the phase of NPN-0.015BT, XRD test was carried out. Figure 1 The characteristic diffraction peaks of NPN-0.015BT shown are consistent with the standard peaks of NaNbO3.
[0062] In order to prove the photoluminescence performance of NPN-0.015BT, PLE and PL tests were carried out. The test results are shown in Figure 8 The excitation spectrum of NPN-0.015BT was obtained under the monitoring wavelength of 610nm. The optimal excitation wavelength was selected as 328nm. The emission wavelength was 580-650nm, which is Pr 3+ of 1 D2- 3 H4 transition, the luminescent color is orange-red.
[0063] In order to prove the stress luminescence performance of stress luminescence materials, conventional stress luminescence tests were carried out. The specific method was as follows: irradiation for 10 minutes under ultraviolet light with a wavelength of 254nm, and then standing in a dark environment for 2 minutes after pre-irradiation. The stress luminescence material was rubbed under a friction force of 15N to test the friction stress luminescence performance. The specific test results are shown in Figure 2. Fig. 9 shown.
[0064] Example 4
[0065] 1) According to the chemical formula Na 0.971 Ba 0.02 Pr 0.003 Nb 0.98 Ti 0.02 O3 was used for mixing, and 5.1458g Na2CO3, 13.0247g Nb2O5, 0.3947g BaCO3, 0.1597g TiO2 and 0.0511g Pr6O 11 Place in an agate ball mill, add 80 ml of anhydrous ethanol, ball mill at a speed of 250 r / min for 10 hours, take out and dry, put into an oven, heat to 850°C at a rate of 8°C / min and keep warm for 8 hours, cool, grind for 50 minutes, put into the oven again, keep warm at 1150°C for 5 hours, cool, grind for 50 minutes, and obtain phosphor (abbreviated as NPN-0.02BT);
[0066] 2) Mixing epoxy resin and polyetheramine in a mass ratio of 8:1, stirring until no bubbles appear in the mixed liquid, to obtain a polymer material;
[0067] 3) The phosphor and polymer material are mixed in a mass ratio of 1:2, and 1.2 g of phosphor and 2.4 g of polymer are weighed;
[0068] 4) After evenly applying vaseline on the inner surface of the polytetrafluoroethylene mold, 1.2 g of phosphor was spread on the bottom of the mold, and 2.4 g of polymer material was added. The mold was allowed to stand at room temperature for 18 min, transferred to an oven, and baked at 75°C for 10 h. After drying, the mold was demolded to obtain the stress luminescent material.
[0069] In order to prove the physical phase of NPN-0.02BT, XRD test was carried out. Figure 1 The characteristic diffraction peaks of NPN-0.02BT shown are consistent with the standard peaks of NaNbO3.
[0070] In order to prove the photoluminescence performance of NPN-0.02BT, PLE and PL tests were carried out. The test results are shown in Fig.10 The excitation spectrum of NPN-0.02BT was tested at a monitoring wavelength of 610nm, and the optimal excitation wavelength was selected as 328nm. The emission wavelength obtained by excitation was 580-650nm, which is Pr 3+ of 1 D2- 3 H4 transition, the luminescent color is orange-red.
[0071] In order to prove the stress luminescence performance of stress luminescence materials, conventional stress luminescence tests were carried out. The specific method was as follows: irradiation for 10 minutes under ultraviolet light with a wavelength of 254nm, and then standing in a dark environment for 2 minutes after pre-irradiation. The stress luminescence material was rubbed under a friction force of 15N to test the friction stress luminescence performance. The specific test results are shown in Figure 2. Fig.11 shown.
[0072] Example 5
[0073] 1) According to the chemical formula Na 0.966 Ba 0.025 Pr 0.003 Nb 0.975 Ti 0.025 O3 was used to prepare the ingredients, and 5.1193g Na2CO3, 12.9582g Nb2O5, 0.4933g BaCO3, 0.1997g TiO2, and 0.0511g Pr6O 11 Place in an agate ball mill, add 80 ml of anhydrous ethanol, ball mill at a speed of 100 r / min for 12 hours, take out and dry, put into an oven, heat to 900°C at a rate of 3°C / min and keep warm for 3 hours, cool, grind for 60 minutes, put into the oven again, keep warm at 1050°C for 6 hours, cool, grind for 30 minutes, and obtain phosphor (abbreviated as NPN-0.025BT);
[0074] 2) Mix epoxy resin and polyetheramine in a mass ratio of 10:1, and stir until no bubbles appear in the mixed liquid to obtain a polymer material;
[0075] 3) The phosphor and polymer materials are mixed in a mass ratio of 1:1; 1.2 g of phosphor and 1.2 g of polymer materials are weighed separately for later use;
[0076] 4) After evenly applying vaseline on the inner surface of the polytetrafluoroethylene mold, 1.2 g of phosphor was spread on the bottom of the mold, and then 1.2 g of polymer material was added. The mold was allowed to stand at room temperature for 10 min, and then transferred to an oven and baked at 80°C for 6 h. After drying, the mold was demolded to obtain the stress luminescent material.
[0077] In order to prove the physical phase of NPN-0.025BT, XRD test was carried out. Figure 1 The characteristic diffraction peaks of NPN-0.025BT shown are consistent with the standard peaks of NaNbO3.
[0078] In order to prove the photoluminescence performance of NPN-0.025BT, PLE and PL tests were carried out. The test results are shown in Fig.12The excitation spectrum of NPN-0.025BT was obtained under the monitoring wavelength of 610nm. The optimal excitation wavelength was selected as 328nm. The emission wavelength was 580-650nm, which is Pr 3+ of 1 D2- 3 H4 transition, the luminescent color is orange-red.
[0079] In order to prove the stress luminescence performance of stress luminescence materials, conventional stress luminescence tests were carried out. The specific method was as follows: irradiation for 10 minutes under ultraviolet light with a wavelength of 254nm, and then standing in a dark environment for 2 minutes after pre-irradiation. The stress luminescence material was rubbed under a friction force of 15N to test the friction stress luminescence performance. The specific test results are shown in Figure 2. Fig.13 shown.
[0080] Comparative Example 1
[0081] 1) According to the chemical formula Na 0.991 Pr 0.003 NbO3 was prepared, and 5.2517 g Na2CO3 and 0.0511 g Pr6O 11 and 13.2905g Nb2O5, placed in an agate ball mill, added 80ml of anhydrous ethanol, ball milled at a speed of 100r / min for 2h, taken out and dried, sent to an oven, heated to 700℃ at a rate of 3℃ / min and kept warm for 3h, cooled, ground for 30min, sent to the oven again, kept warm at 1050℃ for 2h, cooled, ground for 30min, and obtained the phosphor. (abbreviated as NPN-0.00BT)
[0082] 2) Mix epoxy resin and polyetheramine in a mass ratio of 3:1, and stir until no bubbles appear in the mixed liquid to obtain a polymer material;
[0083] 3) The phosphor and polymer material are mixed in a mass ratio of 1:1, and 1.2 g of phosphor and 1.2 g of polymer are weighed respectively;
[0084] 4) After evenly applying vaseline on the inner surface of the polytetrafluoroethylene mold, 1.2 g of phosphor was spread on the bottom of the mold, and then 1.2 g of polymer material was added. The mold was allowed to stand at room temperature for 10 min, transferred to an oven, and baked at 50°C for 6 h. After drying, the mold was demolded to obtain the stress luminescent material.
[0085] In order to prove the phase of NPN-0.00BT, XRD test was carried out. Figure 1The characteristic diffraction peaks of NPN-0.00BT shown are consistent with the standard peaks of NaNbO3, the crystal structure is an orthorhombic phase structure, the space group is P21ma, the doping of BaTiO3 does not affect the synthesis of the crystal phase, and no other impurity phases are observed.
[0086] In order to prove the photoluminescence performance of NPN-0.00BT, PLE and PL tests were carried out. The test results are shown in Figure 2 The excitation spectrum of NPN-0.00BT was obtained under the monitoring wavelength of 610nm. The optimal excitation wavelength was selected as 296nm. The emission wavelength was 580-650nm, which is Pr 3+ of 1 D2- 3 H4 transition, the luminescent color is orange-red.
[0087] In order to prove the stress luminescence performance of stress luminescence materials, conventional stress luminescence tests were carried out. The specific method was as follows: irradiation for 10 minutes under ultraviolet light with a wavelength of 254nm, and then standing in a dark environment for 2 minutes after pre-irradiation. The stress luminescence material was rubbed under a friction force of 15N to test the friction stress luminescence performance. The specific test results are shown in Figure 2. Figure 3 shown.
Claims
1. A praseodymium-doped sodium niobate-barium titanate stress luminescent material, characterized in that: The material is composed of fluorescent powder and polymer material, and the chemical formula of the fluorescent powder is: Na 0.991-x Ba x Pr 0.003 Nb 1-x Ti x O3, x represents the mole fraction, 0.005≤x≤0.025; The polymer material is composed of epoxy resin and polyetheramine, and the mass ratio of the two is 3 to 10:1; The mass ratio of the fluorescent powder to the polymer material is 1:1-5.
2. The praseodymium-doped sodium niobate-barium titanate stress luminescent material according to claim 1, characterized in that: 0.015≤x≤0.025。 3. The praseodymium-doped sodium niobate-barium titanate stress luminescent material according to claim 2, characterized in that: x=0.015。 4. The method for preparing praseodymium-doped sodium niobate-barium titanate stress luminescent material according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) Carbonates Na2CO3, BaCO3, oxide Pr6O 11 , TiO2, Nb2O5 according to the chemical formula Na 0.991-x Ba x Pr 0.003 Nb 1- x Ti x O3 is used for mixing, anhydrous ethanol is used as a solvent for ball milling, and then the phosphor powder is obtained by drying after being taken out, firing for the first time, cooling, grinding for the first time, firing for the second time, cooling, and grinding for the second time. 2) mixing epoxy resin and polyetheramine according to a proportion to obtain a polymer material; 3) Pour the formulated amount of phosphor and polymer material into the mold in sequence, let it stand, dry, and demould to obtain the stress luminescent material.
5. The method for preparing the praseodymium-doped sodium niobate-barium titanate stress luminescent material according to claim 4, characterized in that: In step 1), the ball milling is carried out at a ball milling speed of 100 to 300 r / min for 2 to 12 hours.
6. The method for preparing the praseodymium-doped sodium niobate-barium titanate stress luminescent material according to claim 4, characterized in that: In step 1), the first firing is to increase the temperature to 700-900° C. at a rate of 3-10° C. / min and keep the temperature for 3-9 hours.
7. The method for preparing the praseodymium-doped sodium niobate-barium titanate stress luminescent material according to claim 4, characterized in that: In step 1), the second firing is carried out at 1050-1200° C. for 2-6 hours.
8. The method for preparing the praseodymium-doped sodium niobate-barium titanate stress luminescent material according to claim 4, characterized in that: In step 1), the first grinding time and the second grinding time are both 30 to 60 minutes.
9. The method for preparing the praseodymium-doped sodium niobate-barium titanate stress luminescent material according to claim 4, characterized in that: In step 3), the standing time is 10 to 20 minutes.
10. The method for preparing the praseodymium-doped sodium niobate-barium titanate stress luminescent material according to claim 4, characterized in that: In step 3), the drying temperature is 50-80° C. and the drying time is 6-12 hours.